The Squirrel’s Heartbeat : Review of Ivan Kreilkamp, Minor Creatures: Persons, Animals, and the Victorian Novel - Taylor, Michelle M. (Humanimalia, 2020)
Ivan Kreilkamp, Minor Creatures: Persons, Animals, and the Victorian Novel. Chicago: University of Chicago Press. 240 pp. $90 hb, $30 pb.